PENGUATAN KARAKTER BANGSA MELALUI PEMBINAAN BUDAYA MACAPAT (STUDI DI KELURAHAN BALUWARTI, KECAMATAN PASAR KLIWON, SURAKARTA) - Navitasari, Aurika (Educitizen, 2013)
Citizenship education comes not only include learning experiences in school but also includes learning experiences outside of school or non-formal education / informal. Macapat culture is a means and source of the experiences in the community as an accompanist impact of learning in schools, especially related values. Because Macapat has great value to be developed as civic education rooted in the values education as the essence of civic education to create good citizens and intelligent. Macapat teach human values such as mutual cooperation, tolerance and other civic education as an interdisciplinary approach based on humanities or humanity. Civic education is a vehicle in the formation of character that contribute to education that aims to achieve the formation of the desired character of a citizen of Indonesia or expected by the corresponding values of the noble culture of Indonesia based on Pancasila.